(untitled) (Research, Society and Development, 2023)
Civil construction directly influences other industrial sectors, stimulating the national economy, generating employment, producing inputs, among others. After experiencing different periods of crises, in 2019 the sector started to show positive results. However, in 2020, the world experienced a pandemic scenario due to COVID-19, which resulted in the paralysis of several economic activities, including construction. This situation influenced the costs of construction materials, labor and services in general. In this way, this research sought to analyze the impact that the COVID-19 health crisis had on civil construction costs, with emphasis on small-scale work, using as a model project a single-family single-story residence measuring 80m². The analysis took place from March 2020 to August 2021, showing a total cost burden for the work of approximately R21,878.64, or 14%. Therefore, adequate planning, together with the assistance of qualified professionals, is essential to reduce the impacts caused by moments of crisis, especially in relation to a particular project owner with financial conditions that allow little or no adaptation to cost variations.